2016
DOI: 10.1089/neu.2016.4416
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Previous Comorbidities and Common Complications on Motor Function after Early Surgical Treatment of Patients with Traumatic Spinal Cord Injury

Abstract: The influence of complications and comorbidities on the outcome of patients with traumatic spinal cord injury after early surgery is unclear. The aim of the current study was to analyze the influence of previous comorbidities and common complications on motor function outcome of patients with traumatic spinal cord injury if early surgery was performed. All patients with a traumatic spinal cord injury who were initially surgically treated in our hospital in the period from January 2008 to December 2013 were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is noteworthy that the researchers also indicated that VitD was a negative acute phase reactant, and post-SCI systematic inflammation might decrease the levels of plasma VDBP, which exacerbated VitD insufficiency ( 71 ). Thirdly, SCI patients usually develop multiple complications and comorbidities, such as skeletal diseases, chest illness, neurological sequela, venous thromboembolism, intestinal dysfunction, etc., which may directly result in the lack of VitD or change the lifestyle and affect the level of VitD secondarily ( 72 , 73 ). For example, persons with SCI are likely to develop pressure ulcers and dysregulation of intestinal microflora with significant diet change, which may affect VitD level synergically via impairing its food supply and absorption ( 42 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the researchers also indicated that VitD was a negative acute phase reactant, and post-SCI systematic inflammation might decrease the levels of plasma VDBP, which exacerbated VitD insufficiency ( 71 ). Thirdly, SCI patients usually develop multiple complications and comorbidities, such as skeletal diseases, chest illness, neurological sequela, venous thromboembolism, intestinal dysfunction, etc., which may directly result in the lack of VitD or change the lifestyle and affect the level of VitD secondarily ( 72 , 73 ). For example, persons with SCI are likely to develop pressure ulcers and dysregulation of intestinal microflora with significant diet change, which may affect VitD level synergically via impairing its food supply and absorption ( 42 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of SCI mainly relies on surgical operations and postoperative rehabilitation. However, the recovery of nerve function and the occurrence of complications are still unpredictable (Kreinest et al, 2016). During treatment, multiple system complications could occur, including respiratory failure, pneumonia, bedsores, urinary tract infection (UTI), thromboembolic diseases, and cardiovascular accidents (Maharaj et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In a study of early posterior laminectomy decompression for tSCI (perhaps not extensive decompression), Kreinest reported that pulmonary infection (30.8%) was the most common complication after urinary tract infection (57.9%). [ 22 ] In this study, one potential reason for the reduced rate of respiratory complications may be early extensive decompression leading to early respiratory muscle function recovery, simultaneously avoiding tissue edema and expectoration obstruction caused by tracheal traction in surgery with an anterior approach.…”
Section: Discussionmentioning
confidence: 99%